Defect At Manitoulin Permaculture - Zucca, Matthew (Université d'Ottawa / University of Ottawa, 2019)
The purpose of this research was to describe technopolitics on a permaculture farm. The literature on technology and technopolitics is beginning to take shape around a series of unanswered questions regarding the role and potential of objects in social life. Using an actor-network theory framework and relying on Callon's (1984) sociology of translation and its principles, I identified the concept of defect and tracked how it was mobilized at Manitoulin Permaculture through participant observation across two summers. The concept of defect incorporated both sociopolitical as well as technological factors. The makers at Manitoulin Permaculture made sense of their choice to defect to a new life at Manitoulin Permaculture. In addition, their technologies, both new and old, became defective, animating their community in new and unforeseen ways.
Keywords: Permaculture; Technology; Technopolitics; Farming; Translation; Actor-network